Potential technological use of reserves of Jatropha curcas and J. macrocarpa Griseb. seeds - Tavecchio, Nancy E. de las M.; Dardanelli, Marta S.; Reguera, Yanina B.; Reinoso, Herminda E.; Terenti, Oscar Antonio; Garbero, Marisa M.; Pedranzani, Hilda E. (Scientific Research, 2023)
J. curcas and J. macrocarpa are useful for restoring degraded areas and their seeds contain oils for biodiesel production. The aim of the work was to determine the reserve substances in the endosperm and the embryo of J. curcas and J. macrocarpa which is important in understanding the germination process, the establishment of these species and its industrial employment. Seeds were imbibed in distilled water for 24 h, to facilitate removal of seed coat with the aim to separate the embryo and nutritive tissues. In both species, the endosperm contained aleurone grains consisting of a crystalloid and globoid, lipids of red color and the starch was not observed. Four major fatty acids were determined in J. curcas seed: oleic, palmitic, stearic, palmitoleic and oleic fatty acid represents about 70% oil content. Oleic acid was the most abundant in J. macrocarpa seeds, while, there was not palmitoleic acid. Seed with predominantly unsaturated fatty acids is ideal for biodiesel industry. The means of the sugar content were: 14.3 μg/mg in endosperm and 104.76 μg/mg in embryo of J. curcas and 6.48 μg/mg in endosperm and 59.20 μg/mg in embryo of J. macrocarpa. The means of the protein content were: 4.2 μg/mg in endosperm and 45.02 μg/mg in embryo of J. curcas and 3.26 μg/mg in endosperm and 31.08 μg/mg in embryo of J. macrocarpa. Sugar and protein contents of Jatropha seeds were significantly higher in embryo in both species (p < 0.1), which suggests early mobilization towards the embryo during imbibition period.